Possibilities of use of research-oriented teaching by teachers in technical education - Kozuchova, Maria; Vatral, Peter (Journal of Technology and Information Education, 2022)
In the research study, the authors focus on the state of use of research-oriented teaching in technical education. The main goal of the research was to find out the differences between the state of knowledge and application of research-oriented teaching (BOV) in technical education at the first level of elementary school. Furthermore, we wanted to know how interested teachers are in teaching in a research-based way, how often they use research methods in teaching, and how they prepare for research-based teaching. The results of the research showed that the majority of teachers believe that pupils at the primary level are not capable of independent research, only with the teacher's instructions. The age of the teacher has no effect on the use of BOV, but the more interested the teachers were in science, the higher their tendency to indicate in the questionnaire greater independence of pupils in research. The paper was created with the support of grant VEGA 1/0033/22 Research-oriented teaching in mathematics, science and technical education.
Keywords: research-oriented teaching; education; modernization of technical education; personality of the teacher